ENKULTURASI PERSPEKTIF AL-QUR’AN - N, Abd Muid; B, Muhaemin; Viratama, Terry Arya (Institut PTIQ Jakarta, 2020)
Several issues that can be observed in anthropological and religious view occurred in the relation between culture and religion. Enculturation within this core of study in Qur’anic perspective has several methods that can be used as a dialogical approach between religion and culture which, later, can be applied to the present context. This method of enculturation in Qur'anic perspective has an implied basis in the Qur'an, namely the inculcation of Tauhîd and maslahah which covers all aspects of sharia. From that, the writer try to obtain several ways and approaches in this study to correlate between both culture’s and religion’s conflict that comes afterward.